SUSTAINABILITY OF FAMILY FARMERS ASSOCIATION OF SMALL PRODUCERS OF ALTO SANT'ANA REGION OF SAO JOSE DOS QUATRO MARCOS, MATO GROSSO - Scheuer, Junior Miranda; Alves da Silva Neves, Sandra Mara; Santos Galvanin, Edineia Aparecida dos [UNESP]; Neves, Ronaldo Jose (Fac Metropolitanas Unidas-fmu, 2018)
The objective of this research was to evaluate the level of sustainability of family farming producers of the participants of the Association of Small Producers of Alto Sant'Ana Region in Sao Jose dos Quatro Marcos, Mato Grosso. The methodological procedure used was a semi-structured interview contemplating the environmental, social capital and human, economic and social, family organization and political institutional aspects. To this end, it has developed the Family Agricultural Sustainability Index with the aim of assessing sustainability. The results obtained by means of indices/indicators pointed to a compromised sustainability mainly due to the lack of technical assistance, technology transfer, training school, rural training, etc., although presented variables which have worsened the sustainability. Thus, it was concluded that the result is not only coming from the rural, but to whom the funds, monetarily or politically, leaving the government spheres rethink their plans and include actions aimed at sustainable rural development. Keywords: Rural; Sustainable Development; Indices and Indicators; Agroecology; Public Policy.
Keywords: Rural; Sustainable Development; Indices and Indicators; Agroecology; Public Policy